Kemampuan Tumbuhan Terna dalam Menekan Potensi Inokulum Rigidoporus microporus - Yulianti, Sika; Suwandi, Suwandi; Nurhayati, Nurhayati (Jurnal Fitopatologi Indonesia, 2017)
White root disease caused by Rigidoporus microporus is an important disease of rubber tree and is very difficult to control. The ability of some herbaceous plant species to suppress inoculum potential and infection of R. microporus was studied in a pot trial.  Nine species of herbaceous plants were examined, i.e. arrowroot (Marantha arundinacea), java curcumin (Curcuma xanthorrhiza), sansevieria (Sansevieria fasciata), Mallaca galangal (Alpinia malaccensis), greater galangal (Alpinia galanga), Indian shot (Canna indica), curcumin (Curcuma longa), wild taro (Colocasia esculenta), and water yam (Dioscorea alata). Pathogen’s inocula as mycelial colonizing rubber wood sticks were buried for 90 days in soil planted with tested plants. The results showed that formation of R. microporus rhizomorph in the soil was lower in pots planted with arrowroot, java cucurmin, sansevieria, Indian shot, and wild taro.  All herbaceous plants, except sansevieria, caused suppression of inoculum viability and rhizomorph development.  Further observation showed no colonization of rhizomorph nor necrosis of the root was found, except on Mallaca galangal and sansevieria.